2018
DOI: 10.1111/tri.13108
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of kidney transplantations in children weighing 15 kilograms or less: a retrospective cohort study

Abstract: Kidney transplantation (KT) is often delayed in small children because of fear of postoperative complications. We report early- and long-term outcomes in children transplanted at ≤15 kg in the two largest Belgian pediatric transplant centers. Outcomes before (period 1) and since the introduction of basiliximab and mycophenolate-mofetil in 2000 (period 2) were compared. Seventy-two KTs were realized between 1978 and 2016: 38 in period 1 and 34 in period 2. Organs came from deceased donors in 48 (67%) cases. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
3
18
1
Order By: Relevance
“…The use of our protocol has resulted in both patient and graft survival that compare favorably with recently published studies . In particular, DGF occurred in two (3.2%) patients in our study population, as compared to 6%‐10% reported in prior studies .…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The use of our protocol has resulted in both patient and graft survival that compare favorably with recently published studies . In particular, DGF occurred in two (3.2%) patients in our study population, as compared to 6%‐10% reported in prior studies .…”
Section: Discussionsupporting
confidence: 86%
“…The use of our protocol has resulted in both patient and graft survival that compare favorably with recently published studies . In particular, DGF occurred in two (3.2%) patients in our study population, as compared to 6%‐10% reported in prior studies . Due to multiple factors, ranging from cold ischemia time, hypotension, and donor age, DGF is a significant risk factor for the development of both acute rejection and subsequent graft loss .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations